Analys av mjuka faktorer som påverkar grotuttaget från hygge till avlägg inom Sveaskogs organisation - Ljunglöf, Jenni (SLU/Dept. of Forest Resource Management, 2011)
Biofuels are getting more important as EU plans to replace fossil fuels with renewable energy sources. Because of that Sveaskog has chosen to invest in developing the handling process of logging residue. The company has a joined organisation for handling both round wood and logging residue. They are also working at integrating the forwarding of the logging residue with the rest of the harvesting team. Sveaskog is currently extracting 44 % of the available amount of logging residue. Their goal is to extract 60 %.